2010
DOI: 10.1086/654003
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Control of Endemic Hospital-Wide Methicillin-ResistantStaphylococcus aureus(MRSA): The Impact of Targeted Active Surveillance for MRSA in Patients and Healthcare Workers

Abstract: Our data indicate that long-term control of endemic MRSA is feasible in tertiary care centers. The use of targeted active surveillance for MRSA in patients and healthcare workers in specific wards (identified by means of analysis of clinical epidemiology data) and the use of decolonization were key to the success of the program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…However, despite these system-wide approaches, recent reports suggest an increasing incidence of bacteremia; particularly with gram-negative organisms. [35] These reports indicate that while bacteremia can be reduced by these interventions, many occur despite optimized care and likely reflect factors specific to the individual patient, such as alterations in their immune response, as demonstrated here. We believe that without interventions aimed at injury-induced alterations in both innate and adaptive immunity, system-wide interventions will not eliminate gram-negative bacteremia.…”
Section: Discussionmentioning
confidence: 55%
“…However, despite these system-wide approaches, recent reports suggest an increasing incidence of bacteremia; particularly with gram-negative organisms. [35] These reports indicate that while bacteremia can be reduced by these interventions, many occur despite optimized care and likely reflect factors specific to the individual patient, such as alterations in their immune response, as demonstrated here. We believe that without interventions aimed at injury-induced alterations in both innate and adaptive immunity, system-wide interventions will not eliminate gram-negative bacteremia.…”
Section: Discussionmentioning
confidence: 55%
“…20 Por sua vez, num hospital espanhol, os autores conseguiram uma redução implementando rastreio ativo e descolonização numa população selecionada (doentes admitidos de outras unidades hospitalares) de 0,56 para 0,07 casos por mil dias de internamento. 21 Fraser et al também alcançaram uma redução de 6,38 para 3,32 casos (p = 0,04; RR 0,53; IC95%: 0,28-0,97) por mil dias de internamento ao aplicar rastreio ativo e descolonização numa UCI de 18 camas. 22 Por outro lado, num estudo britânico envolvendo seis hospitais foram levantadas algumas questões relativas à dificuldade de colocar em prática uma estratégia combinada de rastreio ativo e descolonização universal, nomeadamente: dificuldade em rastreio universal (abrangendo somente 88% dos casos) ou no processo de descolonização (atingindo 41% dos casos) devido à mobilidade dos doentes e curta duração dos internamentos, bem como a falta de estrutura física para isolamento dos doentes, deixando dúvidas relativamente ao papel da descolonização na redução do risco no ambiente hospitalar, preferindo frisar a importância das precauções em controlo de infeção.…”
Section: Resultsunclassified
“…In contradistinction, there have been three studies that have had rigorous controls supporting ADI, those by Robicsek, et al [ 11 ], Rodriguez-Bano, et al [ 12 ], and Lee, et al [ 13 ] In addition to isolation, Rodriguez-Bano, et al [ 12 ] and Lee, et al [ 13 ] also decolonized their patients. Lee, et al [ 13 ] also observed that, except in clean surgical wards, ADI and decolonization alone were not effective, nor was enhanced hand hygiene.…”
Section: Reviewmentioning
confidence: 99%